Gender bias in the effect of dropping height on jumping performance in volleyball players - Laffaye, G.; Choukou, M. A. (The Journal of Strength and Conditioning Research, 2010)
The goal of the present study is to investigate in skilled volleyball players (a) the effect of dropping height on women's and men's performance and (b) the drop jump technique with regard to gender. Nine male and 9 female skilled volleyball players were instructed to jump as high as they could, using a drop jump, from a box of 30 cm or from 2 boxes (60 cm). Kinematic and kinetic data were collected using 6 cameras and a force plate. The human body was summarized by using a 4-segment model (foot, shank, thigh, head-arms-trunk). Males performed higher jumps than females (46.6 ± 7.5 cm vs. 36 ± 5.4 cm; p < 0.05). This could be explained by higher mean power (56.9 ± 26 W/kg vs. 42.4 ± 19 W/kg; p < 0.05) and shorter eccentric time (-46.3%), both of which allowed a better stretch-shortening cycle. This study shows that women and men have different jump techniques when they drop from a higher position but without increasing the vertical performance. Women increase the values of force and stiffness (respectively +21.4% and +17.9%) without changing the temporal structure of the jump. Men reduce the eccentric time of the jump (41% vs. 31.8%) and keep the force parameters constant. The study findings indicate that it is necessary to find an optimal height for plyometric training for each athlete, allowing enhancement.